1996
DOI: 10.2307/2988548
|View full text |Cite
|
Sign up to set email alerts
|

Bayesian Methods in Actuarial Science

Abstract: Statistical methods with a Bayesian flavour, in particular credibility theory, have long been used in the insurance industry as part of the process of estimating risks and setting premiums. Typically, however, fully Bayesian analysis has proved computationally infeasible and various approximate solutions have been proposed. The first part of this paper provides a survey of such problems and the kinds of solutions suggested in the actuarial literature. The second part reviews recent advances in Bayesian computa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(29 citation statements)
references
References 33 publications
0
29
0
Order By: Relevance
“…The key principle in Bayesian analysis is that the posterior distribution of a parameter, conditioned on the data, is proportional to the product of its likelihood function and its prior distribution (Gelman et al, 1995, p. 8). Bayesian analysis was intensively studied and its applications cover areas such as econometrics (Gelman et al, 1995), physics (D'Agostini, 2003), health and social sciences (Congdon, 2003), actuarial sciences (Scollnik, 2001;Pai, 1997;Makov et al, 1996;Shapiro, 1979).…”
Section: Bayesian Approach To Fuzzy-stochastic Lee-carter Modelmentioning
confidence: 99%
“…The key principle in Bayesian analysis is that the posterior distribution of a parameter, conditioned on the data, is proportional to the product of its likelihood function and its prior distribution (Gelman et al, 1995, p. 8). Bayesian analysis was intensively studied and its applications cover areas such as econometrics (Gelman et al, 1995), physics (D'Agostini, 2003), health and social sciences (Congdon, 2003), actuarial sciences (Scollnik, 2001;Pai, 1997;Makov et al, 1996;Shapiro, 1979).…”
Section: Bayesian Approach To Fuzzy-stochastic Lee-carter Modelmentioning
confidence: 99%
“…Reviews of the MCMC method, BUGS, and their application in actuarial science can be found in Scollnik (2001). See Makov et al (1996) for a more general discussion of Bayesian methods in actuarial science.…”
Section: Introductionmentioning
confidence: 99%
“…The square-error loss function has been considered in many papers about Bayesian analysis in the risk theory, see Makov et al (1996), Klugman (1992), Klugman et al (1998) for examples. Being symmetric, the square-error loss equally penalizes over-and under-estimation of the same magnitude.…”
Section: Introductionmentioning
confidence: 99%